Correlation between Detergency of Different Oily and Solid Non‐Particulate Soils and Hydrophilic–Lipophilic Deviation. Issue 5 (25th June 2020) - Phaodee, Parichat; Harwell, Jeffrey H.; Sabatini, David A.
Abstract: This research examined the correlation between the detergency of soils with varying equivalent alkane carbon numbers (EACN) and hydrophilic–lipophilic deviation (HLD) values. The detergency of oily soils with EACN ranging from 5.2 to 16.6 was evaluated using C10 ‐4PO‐SO4 Na as a primary surfactant system and a 1:1 binary mixture of C10 ‐4PO‐SO4 Na and AOT as a confirmatory surfactant system (with 65/35 polyester/cotton at 25°C). These surfactant systems were characterized using HLD concepts which showed that C10 ‐4PO‐SO4 Na was more hydrophilic (had a higher negative Cc value) than that of the mixed surfactant system. Detergency of the selected soils was evaluated at different salinities corresponding to HLD ranging from negative to positive values. The results showed that detergency of all soils increased with increasing salinity (starting with an HLD = −3.0 (Winsor Type I microemulsion)), reached the maximum at widely different optimum salinity (S*) but at an identical HLD value of zero (optimum Type III), and then decreased with further increasing salt levels corresponding to positive HLD values (Type II). The preferred HLD range from −3.0 to 0.0 showed detergency levels exceeding 80% removal with interfacial tension values (IFT) below 1 mN m −1 for all oily soils studied. Detergency of octadecane (EACN = 18, solid at 25°C) was further conducted and demonstrated that performing detergency at HLD = −3.0 to 0.0 likewise revealed superior soil removal (over 80%) versus systems with HLD values outside this range. Thus, this work highlighted the utility of using the HLD approach in designing surfactant formulations for detergency of soils with widely varying EACN.